Tyrosine kinase inhibitor-induced carotid stenosis: A case report. (2019) - Hersant, Jeanne; Gardembas, Martine; Leftheriotis, Georges; Vandeputte, Patrick; Abraham, Pierre; Henni, Samir
Abstract: Tyrosine kinase inhibitors are considered as highly effective and relatively safe drugs for the treatment of chronic myeloid leukemia. If several side effects on short and long term are well known and described, their involvement in the development of carotid stenosis remains unclear. Here, we describe a case of carotid stenosis in a patient receiving tyrosine kinase inhibitors and discuss the current literature.